Algerien und Tunesien: Inszenierung und Instrumentalisierung von Märtyrern und Heiligen im frühchristlichen Nordafrika - Bockmann, Ralf (e-Forschungsberichte des DAI, 2023)
The project examines the development of early Christian churches in northern Africa focusing on the cult of martyrs. Because of its rich ecclesiastical heritage and the importance of the martyrial cult the region appears highly suitable for this approach. The project traces the roots of the cult of martyrs as an ancestral cult, and analyses the subsequent integration of the martyrs into the churches as well as the role of bishops and clergy in the developments. The results will be published in a monograph.